Effectiveness of Project-Based Learning with Economic Needs Videos on Elementary School Students Science and Social Science Learning Outcomes - Meidina*, Putri Alifia Nur; Ratnasari, Yuni; Fakhriyah, Fina; Kassymova, Gulzhaina K. (Jurnal IPA & Pembelajaran IPA, 2025)
This study, which was conducted on fourth grade students ar SD Negeri Karangsumber 01 with the goal of analyzing the effectiveness of using the Project-Based Learning model with economic needs videos on Science and Social Science learning outcomes, found that students poor learning outcomes in the Science and Social Science (IPAS) subject are caused by their inability to pay attention to thr teachers explanaton of the material, their lack of engagement during the learning process, and their tendency to get bored easily. A One-Grup Pretest-Posttest research design was employed in this study. Tests, documentation, interviews, and observation were among the methods used to gather data. Paired sample t-tests and N-gain tests were employed as data analysis methods. With a significant value of 0.0000.05, the findings demonstrated that students learning outcomes in Science and Social Science differed. With an N-Gain score of 0.5617 and an N-Gain value of 56.17% the students learning outcomes in Science and Social Science improved, which is considered to be highly effective. With an N-Gain score of 0.6781 and an N-Gain valur of 67.81%, process skills were deemed to be highly successful. This study demonstrates that using the Project-Based Learning paradigm with economic needs videos to teach Science and Social Science subject to fourth-grade elementary school children is highly successful.